Synthesis and Characterization of Bio-based Nanomaterials from Jabon (Anthocephalus cadamba (Roxb.) Miq) Wood Bark: an Organic Waste Material from Community Forest - Sutrisno Sutrisno; Tati Suryati Syamsudin; Eka Mulya Alamsyah; Bambang Sunendar (Journal of Mathematical and Fundamental Sciences, 2015)
The application of nanotechnology to produce nanomaterials from renewable bio-based materials, like wood bark, has great potential to benefit the wood processing industry. To support this issue, we investigated the production of bio-based nanomaterials using conventional balls milling. Jabon (Anthocephalus cadamba (Roxb.) Miq) wood bark (JWB), an organic waste material from a community forest was subjected to conventional balls milling for 96 h and was converted into bio-based nanomaterial. The morphology and particle size, chemical components, functional groups and crystallinity of the bio-based nanomaterial were evaluated using scanning electron microscopy (SEM), scanning electron microscopy extended with energy dispersive X-ray spectroscopy (SEM-EDS), Fourier transform infrared spectroscopy (FTIR), and X-ray diffraction (XRD). The particle-sizes obtained for the JWB bio-based nanomaterial were between 43 nm to 469 nm and the functional groups were detected as cellulose. The chemical components found were carbon, oxygen, chloride, potassium and calcium, except for the sample produced from sieve type T14, which did not contain chloride. The crystalline structure was calcium oxalate hydrate (C2CaO4.H2O) with crystalline sizes 21 nm and 15 nm, produced from sieve types T14 and T200 respectively.